The foreign policy of the United States of America towards Western Europe for the period 1945-1950 - Sukkar Khayoon, Bushra (Journal of College of Education, 2022)
Abstract: One of the results of World War II was the emergence of America, which is one of the countries with economic and military capabilities, in other words, one of the countries with political, economic and military capabilities, at a time when some of the major powers in this aspect, including the United Kingdom, retreated, which forced the Americans to adopt a new global strategy that fits  With the nature of the variables produced by the post-war phase due to the emergence of a competing international power, the communist bloc, which formed a competing bloc, while the United States of America led the capitalist bloc, and the two blocs sought to win the largest number of countries in their favor at the expense of the other, which was discussed in this  Subject.
Keywords: America, strategy